A COMPARATIVE STUDY OF MAGNASIUM SULFATE IN TREATING PEDIATRIC ACUTE BRONCHIOLITIS - Hussain, Ansar; Ahmad, Khalil; Gul, Haji; Ibrahim, Muhammad; Rehman , Habib Ur; Khan, Muhammad Rafiq (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute bronchiolitis is a common respiratory disease in children that often necessitates hospitalization. Treatments for this condition include bronchodilators and supportive care. Although magnesium sulfate and hypertonic saline have been proposed as possible therapies, it is yet unknown how successful they are in comparison. This study aimed to compare the clinical efficacy, safety, and impact on respiratory outcomes of nebulized magnesium sulfate versus hypertonic saline in treating pediatric acute bronchiolitis. Methods: A prospective cohort study was conducted at Bannu Medical College, MTI Bannu, from January to December 2023. A total of 120 children (ages 2 months to 2 years) diagnosed with acute bronchiolitis were randomly assigned into two groups: Group A received nebulized magnesium sulfate (0.1cc/kg of 50% solution) every 8 hours for 24 hours, while Group B received nebulized hypertonic saline (3%, 4cc) every 8 hours for 24 hours. Both groups received standard supportive care. Primary outcomes included improvements in respiratory distress scores, oxygen saturation, wheezing, and respiratory rate. Secondary outcomes assessed hospital stay duration, side effects, and the need for additional treatment. Data were analyzed using independent t-tests for continuous variables and chi-square tests for categorical variables, with statistical significance set at p<0.05. Results: Both treatments significantly improved respiratory distress scores and oxygenation. However, Group A (magnesium sulfate) showed greater reductions in wheezing and respiratory rate compared to Group B (hypertonic saline) (p<0.05). Additionally, hospital stay duration was shorter in Group A (mean±SD: 3.2±0.9 days) compared to Group B (3.8±1.1 days, p=0.03). No severe side effects were observed in either group. Conclusion: Nebulized magnesium sulfate demonstrated superior efficacy in improving respiratory distress and reducing hospital stay duration compared to hypertonic saline, suggesting its potential as a more effective treatment option for pediatric acute bronchiolitis. These findings highlight the need for further large-scale randomized controlled trials to confirm these results and refine treatment protocols.